(untitled) (Bangladesh Journal of Agricultural Research, 2022)
Strawberry plants were grown in five different mixtures of coco-dust and gravel to compare their influences under glasshouse condition at hydroponics and controlled environment agriculture research facilities of Olericulture division, HRC, BARI, Gazipur during winter season. The experimental design was completely randomized block design with 10 replicated plants/pots. The plants were supplied with 25% ‘Enshi-shoo’ nutrient solution in every alternative day. Strawberry plants were grown in five different mixtures of coco-dust and gravel substrates as T1 (100:0), T2 (75:25), T3 (50:50), T4 (25:75) and T5 (0:100). Results showed that coco-dust and gravel substrate had significant influence on number of leaves, root length and root dry weight. Root length was found to be hampered greatly in plants grown with sole gravel substrate because of its poor moisture holding capacity. Fruit yield per plant was higher in T3 (50:50 of cocodust and gravel) compared to other substrate mixtures. The present study revealed that the growth, yield and fruit qualities were significantly higher in plants grown in 50:50 of coco-dust and gravel compared to their other mixture substrates. Bangladesh J. Agril. Res. 45(2): 199-207, June 2020